Dyslipidemia and Risk of Cardiovascular Events in Patients With Atrial Fibrillation Treated With Oral Anticoagulation Therapy: Insights From the ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation) Trial. Issue 3 (1st February 2018) - Pol, Tymon; Held, Claes; Westerbergh, Johan; Lindbäck, Johan; Alexander, John H.; Alings, Marco; Erol, Cetin; Goto, Shinya; Halvorsen, Sigrun; Huber, Kurt; Hanna, Michael; Lopes, Renato D.; et al.
Abstract : Background: Dyslipidemia is a major risk factor for cardiovascular events. The prognostic importance of lipoproteins in patients with atrial fibrillation is not well understood. We aimed to explore the association between apolipoprotein A1 (ApoA1) and B (ApoB) and cardiovascular events in patients with atrial fibrillation receiving oral anticoagulation. Methods and Results: Using data from the ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation) trial, ApoA1 and ApoB plasma levels were measured at baseline in 14 884 atrial fibrillation patients. Median length of follow‐up was 1.9 years. Relationships between continuous levels of ApoA1 and ApoB and clinical outcomes were evaluated using Cox models adjusted for cardiovascular risk factors, medication including statins, and cardiovascular biomarkers. A composite ischemic outcome (ischemic stroke, systemic embolism, myocardial infarction, and cardiovascular death) was used as the primary end point. Median (25th, 75th) ApoA1 and ApoB levels were 1.10 (0.93, 1.30) and 0.70 g/L (0.55, 0.85), respectively. In adjusted analyses, higher levels of ApoA1 were independently associated with a lower risk of the composite ischemic outcome (hazard ratio, 0.81; P <0.0001). Similar results were observed for the individual components of the composite outcome. ApoB was not significantly associated with the composite ischemic outcome ( P =0.8240). Neither apolipoprotein was significantly associated with major bleeding. There was no interaction between lipoproteins and randomized treatment for the primary outcome (both P values ≥0.2448). Conclusions: In patients with atrial fibrillation on oral anticoagulation, higher levels of ApoA1 were independently associated with lower risk of ischemic cardiovascular outcomes. Investigating therapies targeting dyslipidemia may thus be useful to improve cardiovascular outcomes in patients with atrial fibrillation. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00412984.